Melatonin duration gates photoperiodic vocal state change in a songbird. Issue 2 (18th December 2019) - Harpole, Clifford E.; Miles, Meredith D.; Cassone, Vincent M.
Abstract: Seasonally breeding animals concentrate courtship to a particular time of year such that their offspring will be reared in a favorable environment. In house sparrows, Passer domesticus, primary (gonads) and secondary (song, plumage, beak color, etc) sexual characteristics are expressed differentially depending on the photoperiod. Removal of the pineal gland (PINX) has no effect on seasonal rhythms in gonad size but alters the photostimulated increase in vocal rate and complexity. Administration of long durations of melatonin, indicative of short days of winter, prevents seasonal recrudescence of song control nuclei in photostimulated house sparrows. In this study, male PINX house sparrows were exposed to three durations of melatonin, while vocalization and locomotor behavior were recorded as they were transitioned from short photoperiod to equinoctial photoperiods of spring. Birds receiving short duration melatonin or vehicle control increased dawn and dusk choruses as well as call complexity. Long durations of melatonin prevented this expansion to a spring‐like vocal state observed in birds receiving the short duration of melatonin or vehicle control. The daily distribution of locomotor activity, beak color, and testis size was unaffected by treatment. Vocal state change was defined by our measures in two capacities: (i) increased dawn and dusk choruses, and (ii) an increase in calls associated with territory and mate attraction compared to the winter‐like "social song." We conclude that house sparrows use the calendar information provided by melatonin duration to control seasonal vocalization behavior, independent of effects on and of the gonads.